p38/Sp1/Sp4/HDAC4/BDNF Axis Is a Novel Molecular Pathway of the Neurotoxic Effect of the Methylmercury - Guida, Natascia; Laudati, Giusy; Mascolo, Luigi; Valsecchi, Valeria; Sirabella, Rossana; Selleri, Carmine; Di Renzo, Gianfranco; Canzoniero, Lorella M. T.; Formisano, Luigi (Frontiers in Neuroscience, 2017)
The molecular pathways involved in methylmercury (MeHg)-induced neurotoxicity are not fully understood. Since pan-Histone deacetylases (HDACs) inhibition has been found to revert the neurodetrimental effect of MeHg, it appeared of interest to investigate whether the pattern of HDACs isoform protein expression is modified during MeHg-induced neurotoxicity and the transcriptional/transductional mechanisms involved. SH-SY5Y neuroblastoma cells treated with MeHg 1 μM for 12 and 24 hours showed a significant increase of HDAC4 protein and gene expression, whereas the HDACs isoforms 1-3, 5 and 6 were unmodified. Furthermore, MeHg-induced HDAC4 increase was reverted when cells were transfected with siRNAs against specificity protein 1 (Sp1) and Sp4, that were both increased during MeHg exposure. Next we studied the role of extracellular-signal-regulated kinases 1/2 (ERK1/2), c-Jun N-terminal kinases (JNK), and p38 mitogen-activated protein kinases (MAPKs) in MeHg – induced increase of Sp1, Sp4 and HDAC4 expression. As shown by Western Blot analysis MeHg exposure increased the phosphorylation of p38, but not of ERK and JNK. Notably, when p38 was pharmacologically blocked, MeHg-induced Sp1, Sp4 protein expression and HDAC4 protein and gene expression was reverted. In addition, MeHg exposure increased the binding of HDAC4 to the promoter IV of the Brain-derived neurotrophic factor (BDNF) gene, determining its mRNA reduction, that was significantly counteracted by HDAC4 knocking down. Furthermore, rat cortical neurons exposed to MeHg (1 μM/24h) showed an increased phosphorylation of p38, in parallel with an up-regulation of Sp1, Sp4, and HDAC4 and a down-regulation of BDNF proteins. Importantly, transfection of siRNAs against p38, Sp1, Sp4 and HDAC4 or transfection of vector overexpressing BDNF significantly blocked MeHg-induced cell death in cortical neurons. All these results suggest that p38/Sp1-Sp4/HDAC4/BDNF may represent a new pathway involved in MeHg-induced neurotoxicity.